Cover Picture: Discovery of New Classes of Compounds that Reactivate Acetylcholinesterase Inhibited by Organophosphates (ChemBioChem 15/2015). Issue 15 (October 2015) - Katz, Francine S.; Pecic, Stevan; Tran, Timothy H.; Trakht, Ilya; Schneider, Laura; Zhu, Zhengxiang; Ton‐That, Long; Luzac, Michal; Zlatanic, Viktor; Damera, Shivani; Macdonald, Joanne; Landry, Donald W.; et al.
<x xml:space="preserve">Abstract</x> The cover picture shows that a mouse exposed to otherwise lethal doses of an organophosphorous agent survives if it is treated with compounds that we recently identified as reactivators of organopsphate‐inhibited acetylcholinesterase (AChE). We have demonstrated that survival correlates with reactivation of AChE activity across a panel of tissues, including brain tissues across the blood–brain barrier. We have also determined the co‐crystal of one of these reactivators bound to organophosphate‐inhibited AChE and found that it binds in a unique manner to the enzyme, forming a dimer within the active site. These compounds were also efficient at reactivating the human form of AChE, thus indicating that their protective effects could be translated for human use. Molecular graphics for the cover were performed with the UCSF Chimera package. Chimera is developed by the Resource for Biocomputing, Visualization, and Informatics at the University of California, San Francisco (supported by NIGMS P41‐GM103311).